Endocrine Disrupting Chemicals: Effects on Endocrine Glands - Lauretta, Rosa; Sansone, Andrea; Sansone, Massimiliano; Romanelli, Francesco; Appetecchia, Marialuisa (Frontiers in Endocrinology, 2019)
In recent years endocrine disrupting chemicals have gained interest in human physiopathology and more and more studies aimed to explain how these chemicals compounds affect endocrine system. In human populations, the majority of the studies point towards an association between exposure to endocrine disrupting chemicals and the disorders affecting endocrine axis. A great number of endocrine disrupting chemicals seems to be able to interfere with the physiology of hypothalamus-pituitary-gonadal axis; however, every endocrine axis may be a target for each EDCs and their action is not limited to a single axis or organ. Several compounds may also have a negative impact on energy metabolic homeostasis altering adipose tissue and promoting obesity, metabolic syndrome, and diabetes. Different mechanism have been proposed to explain these associations but their complexity together with the degree of occupational or environmental exposure, the low standardization of the studies, and the presence of confounding factors have prevented to establish causal relationship between the endocrine disorders and exposure to specific toxicants so far. This manuscript aim to review the state of art of scientific literature regarding the effects of endocrine-disrupting chemicals on endocrine system.